Relevansi adopsi manajemen Jepang dalam kerangka pengembangan sumber daya manusia dan industrialisasi di Indonesia: Pendekatan proses dan keterkaitan ekonomi - Akhmad Muhadi (Universitas Islam Indonesia, 1997)
TheJapanese transplants in Indonesia have been playing an important role on the process of industrialization in Indonesia. As the